Change of Serum Metabolome and Cecal Microflora in Broiler Chickens Supplemented With Grape Seed Extracts - Cao, Guangtian; Zeng, Xinfu; Liu, Jinsong; Yan, Feifei; Xiang, Zhentian; Wang, Yongxia; Tao, Fei; Yang, Caimei (Frontiers in Immunology, 2020)
Grape seed is rich in vitamin E, flavonoids, and proanthocyanidins and has the potential to be used as an antibiotic substitute in broilers. We investigated the effects of grape seed proanthocyanidin extract (GSPE) on growth performance, immune responses, cecal microflora, and serum metabolism in early stage broilers. Data indicated that GSPE improved broiler growth performance by strengthening antioxidant capacity, enhancing immune responses, and increasing cecal short chain fatty acids. 16S rRNA sequencing indicated that GSPE changed the predominant cecal microflora and induced the metabolism of amino acids, lipids, and carbohydrates. An UPLC-Q-TOF/MS-based metabolomics analysis identified 23 serum metabolites (mainly related to lipid, amino acid, and alkaloid) were extremely changed by GSPE treatment. The correlations between the changes of cecal microflora and serum metabolites in birds fed with GSPE were analyzed. Hence, GSPE potentially provides active ingredients that may be used as antibiotic substitute and reduces environmental pollution by grape by-products.